2002
DOI: 10.1097/00000539-200205000-00023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fentanyl on the Emergence Characteristics After Desflurane or Sevoflurane Anesthesia in Children

Abstract: The concurrent use of fentanyl in a dose of 2.5 microg/kg in children receiving desflurane or sevoflurane results in a low incidence of emergence agitation. Desflurane allows for a more rapid emergence and recovery than sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
4
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 16 publications
5
87
4
6
Order By: Relevance
“…16,17 Our results are consistent with these findings despite the fact that these previous studies differed in their use of nitrous oxide for anesthesia induction and maintenance. Nevertheless, few studies have compared anesthesia emergence times between desflurane and sevoflurane after volatile induction in adults.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16,17 Our results are consistent with these findings despite the fact that these previous studies differed in their use of nitrous oxide for anesthesia induction and maintenance. Nevertheless, few studies have compared anesthesia emergence times between desflurane and sevoflurane after volatile induction in adults.…”
Section: Discussionsupporting
confidence: 90%
“…This is most likely due to the young age of the participants in prior studies, which prevented precise measurements of recovery times. 16,17 The times in our study from discontinuation of volatile anesthetics to orientation to the patients' full name, date, and place were significantly shorter in the desflurane group than in the sevoflurane group, which suggests that changing from sevoflurane to desflurane permits faster recovery than sevoflurane anesthesia, even after sevoflurane induction. In addition, the time trend in recovery events differed between the two groups.…”
Section: Discussionmentioning
confidence: 66%
“…Fentanyl 2.5 lg.kg À1 has been shown to reduce the incidence of severe ED without a delay in emergence [35,36]. Kim ] following desflurane anaesthesia [19].…”
Section: Time (Min)mentioning
confidence: 99%
“…Dong et al, found that intraoperative remifentanil decreased the incidence of ED in children undergoing adenotonsillectomy [60]. Fentanyl, given either IV 2.5 μg/kg or intranasally 2 μg/kg during moderately painful surgery, has also been shown to decrease emergence agitation in children [61][62][63][64]. Bong et al, confirmed the preventative effects of fentanyl and further identified a lack of fentanyl as an independent risk factor for ED [34].…”
Section: Nsaids and Opioidsmentioning
confidence: 99%